Fluoride Induces a Volume Reduction in CA1 Hippocampal Slices Via MAP Kinase Pathway Through Volume Regulated Anion Channels - Lee, Jaekwang (Exp Neurobiol, 2016)
Regulation of cell volume is an important aspect of cellular homeostasis during neural activity. This volume regulation is thought to be mediated by activation of specific transporters, aquaporin, and volume regulated anion channels (VRAC). In cultured astrocytes, it was reported that swelling-induced mitogen-activated protein (MAP) kinase activation is required to open VRAC, which are thought to be important in regulatory volume decrease and in the response of CNS to trauma and excitotoxicity. It has been also described that sodium fluoride (NaF), a recognized G-protein activator and protein phosphatase inhibitor, leads to a significant MAP kinase activation in endothelial cells. However, NaF's effect in volume regulation in the brain is not known yet. Here, we investigated the mechanism of NaF-induced volume change in rat and mouse hippocampal slices using intrinsic optical signal (IOS) recording, in which we measured relative changes in intracellular and extracellular volume as changes in light transmittance through brain slices. We found that NaF (1~5 mM) application induced a reduction in light transmittance (decreased volume) in CA1 hippocampus, which was completely reversed by MAP kinase inhibitor U0126 (10 µM). We also observed that NaF-induced volume reduction was blocked by anion channel blockers, suggesting that NaF-induced volume reduction could be mediated by VRAC. Overall, our results propose a novel molecular mechanism of NaF-induced volume reduction via MAP kinase signaling pathway by activation of VRAC.